PRELIMINARY DEMOGRAPHIC TRENDS IN ORAL FUNCTION DECLINE: AGE AND SEX DIFFERENCES IN TOOTH LOSS AMONG OLDER ADULTS - Ni Putu Idaryati; Yudha Rahina; I Ny Panji Triadnya Palgunadi; I Gusti Agung Ayu Chandra Iswari Dewi; Luh Putu Eka Sriwijayanti (FKG ULM, 2026)
Background: Tooth loss (edentulism) is a common oral health problem among older adults that negatively affects chewing ability, aesthetics, and quality of life. Posterior teeth, particularly molars, are more susceptible to loss due to their functional load and anatomical position. Biological factors such as age and gender may contribute to variations in tooth loss; however, community-level evidence remains limited in specific local settings.Purpose: This study aimed to describe the pattern of tooth loss and explore its potential association with age and gender among elderly individuals in Banjar Kebon Kori, Kelurahan Kesiman, East Denpasar.Methods: A descriptive observational study was conducted involving 17 elderly participants selected through total sampling. Data were collected through direct clinical oral examinations. Statistical analysis was primarily descriptive (frequency and percentage), and bivariate analysis was performed using Fisher’s Exact Test due to the small sample size. Results: Tooth loss was predominantly observed in posterior teeth, particularly the first molars (21.6%). Females showed a slightly higher proportion of tooth loss (53.4%) compared to males (46.6%). A higher proportion of tooth loss was also observed among participants aged ≥70 years compared to those aged 60–69 years. However, these findings should be interpreted with caution due to the small sample size (n = 17) and unequal group distribution. Conclusion: This study suggests that tooth loss among elderly individuals tends to be more frequent in posterior teeth and may vary according to age and gender. However, the findings are exploratory and do not establish causal relationships. Further studies with larger and more representative samples are needed to confirm these observations.Keywords: Age, Elderly, Gender, Posterior teeth, Tooth loss.